Impactos da pandemia de COVID-19 no setor hoteleiro: os casos de Lisboa, Maputo e São Paulo - Rita de Cássia Ariza da Cruz; Eduardo Brito-Henriques; Sara Larrabure; Dário Manuel Isidoro Chundo (Confins)
This paper seeks to do an exploratory analysis of the changes observed in the hotel sector in three cities in three different countries and continents. Joining information from official databases, direct survey in hotels and hotel websites, and interviews with industry representatives, an inventory and analysis of the changes observed in hotel supply in Lisbon (Portugal), Maputo (Mozambique) and São Paulo (Brazil) throughout 2020 and 2021 is made. Results show that suspension of activity, with temporary closure during the most critical periods of the pandemic, and partial reduction of supply to reduce operational costs, were the most common strategies followed by hotels in the three cities, with consequences in job losses. Other changes of a more structural nature, such as rebranding processes and permanent closure of hotels found significant variations among the cities studied. The adoption of different policy measures in the various countries and their varying exposure to international tourism explain partly these differences.